Nano : The Essentials Understanding Nanoscience and Nanotechnology - Pradeep T (New Delhi Tata Mc Graw Hill Education Private Limited, 2007)
It begins with a historical introduction to Nano along with a brief review of various experimental tools used to understand nanoscale materials. This is followed by a discussion of selected nanomaterials, ranging from fullerenes and nanotubes to nanoshells. Subsequently several areas of application of nanoscience such as nanosensors and nanobiology are covered. The book concludes with an analysis of the societal implications of nanoscience and technology, particularly of relevance to developing countries.
Keywords: NANO SCIENCE -- NANO TECHNOLOGY -- NANO STRUCTURES